Mortgage lending targets of housing policy in Russia - A. N. Lozovskaya; M. A. Skorik (Статистика и экономика, 2018)
The regular socio-economic monitoring studies are really essentialwith the purpose of development of an effective system for housing development sector support at the state level and of account of the diversity of factors, which impact the change of housing  conditions of population. With this purpose, the authors performed  benchmarking statistical analysis of the state and trends in the  development of housing construction and housing provision in  various regions of Russia, taking into account the availability of  housing and the degree of tension in the housing and social sphere,  as well as the opportunities, which are provided for the population to settle the housing issue through property lending The economic  crisis could not relieve the "housing problem" for Russians, but only  gave rise to housing deferred demand. Therefore, the researches are still timely of the housing policy development directions and of the  solution of the housing problems, as well as of the housing lending  system. In addition to solving the population housing affordability  problem, the intensification of property lending policy directly affects the of new housing supply index of various degree of conventions.  This is achieved through engaging of significant amounts of money  by the population. The subject of the research is a set of indices of  the conditions and of level of development of housing construction and related property lending. The information base of the research is the official data of the Federal State Statistics Service, of the Bank of Russia, as well as the materials of scientific publications and  periodicals on the subject Statistical methods for identifying the  trends and the cycles, for study of economic conditions and business activity, for analysis of structural breaks, for time series forecasting,  as well as the tabular and graphical methods for visual  representation of data are used as the main statistical tools. In  accordance with the aim, the authors set and solved the tasks  as  follows: – the main features, problems and trends are specified in  the development of housing constructions in the Russian Federation  and its subjects;– regional differentiation is estimated in the level of housing provision of population and in the changes in its living conditions,  taking into account the impact of crisis phenomena;– the intensity and directions are determined the of structural changes in the regional distribution of the total volume of housing;– the groups of the Russian regions are revealed, which are differed by the main characteristics of housing conditions of the population and by the scale and activity of housing construction;– the factors and criteria are considered of efficiency of housing property lending and a role of regional banks in this process;– the main problems are revealed, which constrain lending development in Russia.The results of the research are of practical importance for the Federal State Statistics Service in the course of monitoring of the  state of the housing complex at the regional level, as well as for  regional economic agencies in the development of programs for  support and development of the housing construction sector.